Assessment of the properties of diethyl phosphite as a novel anticorrosion pigment in organic coatings - Nechvílová, Kateřina; Kalendová, Andréa; Schmidová, Eva; Bober, Patrycja (Springer, 2017)
The aim of this work was to provide a first description of the behaviour of diethyl phosphite in organic coatings, description of their physico-mechanical properties as well as anticorrosion properties in the protection of steel substrates. The diethyl phosphite behaviour in the organic coatings depends on the volume concentration of the pigment. A polyaniline base was suspended in diethyl phosphite as a new reactant. The pigment so prepared was used as a corrosion inhibitor in model paints containing a solvent-based epoxy-ester resin as the binder. The organic coatings were applied to steel panels and to glass panels and subjected to mechanical tests, corrosion resistance tests and electrochemical tests. Furthermore, they were exposed to the environments of condensed steam, neutral salt solution mist, and sulphur dioxide-containing mist. The corrosion effects were evaluated and the organic coatings' overall anticorrosion efficiency was calculated from the results. Ultimately, the optimum pigment volume concentration (PVC) at which the coatings provided the best anticorrosion protection was determined: it was PVC = 10 vol%, whereas the best mechanical resistance was observed at PVC = 5 vol%. The goal of the forthcoming work will be to optimise all the properties into a single pigment volume concentration.
Hodnocení vlastností Diethylfosfitu ve funkci nového antikorozního pigmentu v organických nátěrech
Keywords: Diethyl phosphite; Conductive polymers; Polyaniline; Organic coatings; Diethypfosfit; vodivé polymery; polyanilin; organické povlaky